iPad and iPad Pro - McFedries, Paul (--For dummies., 2024)
Fully updated to cover the latest version of iPadOS and all the newest features, iPad & iPad Pro For Dummies is your fun, full-color guide to the most popular tablet on the market. There are a lot of things you can do with an iPad?browse the internet, take photos and videos, manage your schedule, play games, stream media, create documents, send e-mail, and beyond. Learn how to tackle everything from the basics to more advanced iPad operations, and find tips on how to make the most of the new features and customize your device to your liking. You?re on your way to becoming an iPad power user, with this Dummies title.